PEMBANGUNAN PARIWISATA DAERAH MELALUI PENGEMBANGAN SUMBER DAYA MANUSIA DI GORONTALO - Anugrah, Krishna; Sudarmayasa, I Wayan (Jurnal Master Pariwisata (JUMPA), 2017)
This study discusses about development of regional tourism through the development of human resources Gorontalo, Sulawesi. The master plan for tourism development in Gorontalo stated that Gorontalo has three areas of community-based tourism development and eight excellent tourist attractions. It was realised that human resources has an important role in the general development as well the development of regional tourism. The approach used in this research is descriptive qualitative, data source obtained from field observation, interview, group discussion and documentation. Local governments have encouraged the development of regional tourism, especially destinations that are around the community through the empowerment of surrounding communities in order to manage the destination well. In order for all aspects of tourism management to run properly it is necessary role of local government in giving encourage and support education field of tourism. So it can fill the shorted of expert workforce to be placed on institutions or tourism related industries.